DECLINING SYSTEMIC TRUST IN THE POLITICAL ELITE IN THE EU’S NEW MEMBER STATES: THE DIVERGENCE BETWEEN EAST-CENTRAL EUROPE AND THE BALTIC STATES - Ágh, Attila (Baltic Journal of Political Science, 2018)
In the last decade there has been a process of rolling-back Europeanization efforts in the EU’s new member states (NMS), a process intensified by the global crisis. This de-Europeanization and de-democratization process in the NMS has become a significant part of a more general polycrisis in the EU. The backslide of democracy in the NMS as a topical issue has usually been analysed in terms of macro-politics, formal-legal state institutions, party systems, and macroeconomics. The most significant decline of democratization, however, is evident in the public’s decreasing participation in politics and in the eroding trust. This decline in systemic trust in political elites in the NMS has been largely neglected by analysts. Therefore, this paper concentrates on this relatively overlooked dimension of declining trust and social capital in the NMS. This analysis employs the concepts of governance, trust, and social capital to balance the usual formalistic top-down approach with a bottom-up approach that better illustrates the divergence between East-Central Europe and the Baltic states’ sub-regional development.